A comparison of the personality and background characteristics of adolescent sex offenders and other adolescent offenders - Oliver, Lori L. (Criminal justice and behavior, 1993)
The current study investigated personality differences between adolescent sex offenders and nonsexually offending adolescents on the Jesness Inventory. Subjects were 50 adolescent males charged with a sexual offense, 50 adolescent males charged with nonviolent offenses, and 50 adolescent males charged with violent offenses. The adolescent sex offender group generally displayed the least deviant personality and historical characteristics among the groups examined. These findings, inconsistent with the adult sex offender literature, suggest that sex offenders may be more amendable to treatment during adolescence than during adulthood and that early intervention may have preventive value